PENGARUH FLASH SALE, PAYLATER, DAN FOMO TERHADAP PERILAKU IMPULSE BUYING PADA PLATFORM E-COMMERCE DI WILAYAH JAKARTA DAN BEKASI - Wuryan, Sophiyanto; Amel, Dika Amelia; Baskara, Ika (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of flash sales, paylater, and fear of missing out (FOMO) on impulse buying behavior on e-commerce platforms in Indonesia, focusing on TikTok Shop. The increasing trend of online shopping has encouraged spontaneous buying behavior due to promotional strategies that create a sense of urgency and provide ease of transaction. This study used a quantitative approach with a survey method by distributing questionnaires to 125 respondents who were TikTok Shop users in the Jakarta and Bekasi areas. The sampling technique used purposive sampling, while data analysis used multiple linear regression using SPSS version 23. The results showed that flash sales, paylater, and FOMO had a positive and significant influence on impulse buying, both partially and simultaneously. Of the three variables, paylater proved to have the most dominant influence on impulsive buying behavior. These findings provide managerial implications for e-commerce players to strengthen promotional strategies that emphasize a sense of urgency and ease of payment to encourage spontaneous consumer purchasing decisions.